2011
DOI: 10.1177/0142723711403980
|View full text |Cite
|
Sign up to set email alerts
|

Overt subjects and copula omission in the Spanish and the English grammar of English–Spanish bilinguals: On the locus and directionality of interlinguistic influence

Abstract: The presence of non-adult patterns of omission/production of functional categories has occupied a central place in both monolingual and bilingual child language acquisition research. In bilingual acquisition a central learnability issue has been to determine whether interlinguistic influence would interact with those patterns. In this article, the authors analyse the omission/production of subject pronouns in the developing Spanish grammar and of copula be in the developing English grammar of two EnglishSpanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 48 publications
2
53
1
Order By: Relevance
“…Therefore, cross-linguistic influence should occur from Italian (the most transparent system) to German (the least transparent one with respect to the phenomenon at stake), and not vice versa (see Section 1 for further details), contrary to what is predicted by the accounts reviewed previously. In support of this hypothesis, Liceras et al (2012) found no overuse of overt subjects in Spanish by English-Spanish simultaneous bilinguals. Rather, the authors show that among young simultaneous English-Spanish bilinguals, the transparency of the Spanish system favors the acquisition of sentential subjects in English.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Therefore, cross-linguistic influence should occur from Italian (the most transparent system) to German (the least transparent one with respect to the phenomenon at stake), and not vice versa (see Section 1 for further details), contrary to what is predicted by the accounts reviewed previously. In support of this hypothesis, Liceras et al (2012) found no overuse of overt subjects in Spanish by English-Spanish simultaneous bilinguals. Rather, the authors show that among young simultaneous English-Spanish bilinguals, the transparency of the Spanish system favors the acquisition of sentential subjects in English.…”
Section: Introductionsupporting
confidence: 53%
“…Structural account (e.g., Müller and Hulk 2001) overuse of overt pronouns in subject position and production of null objects (alias, clitic omissions) b. Morphosyntactic complexity account (e.g., Liceras et al 2012).…”
Section: Account Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Serratrice and Hervé (2015) note, the studies conducted by Juan-Garau and Pérez-Vidal (2000), , SilvaCorvalán (2014), and Zwanziger et al (2005) did not find evidence in support of CLI based on the relative proportion of null and overt subjects in children's naturalistic productions (see also Gutiérrez-Clellen, Simon-Cerejido, andWagner, 2008 andLiceras et al, 2012); their performance regarding the rate of non-overt and lexical subjects was reminiscent of that of monolinguals, challenging the CLI hypothesis. Nonetheless, Serratrice and Hervé (2015) emphasize the need to investigate the issue of whether subjects are pragmatically appropriate, since CLI is tightly connected to the interface between syntax and semantics/pragmatics, a consideration that was indeed taken into account by some studies.…”
Section: The Crosslinguistic Influence Hypothesis Regarding Subjecthoodmentioning
confidence: 96%
“…Children's acquisition of the Spanish copulas ser and estar has been the focus of a number of recent studies (Alonqueo & Soto, 2011;Alonqueo, 2007;Holtheuer et al, 2011;Holtheuer & Rendle-Short, 2013;Holtheuer, 2009;Holtheuer, 2013;Liceras, Fernández-Fuertes & Alba de la Fuente, 2012;Requena et al, 2014;Schmitt & Miller, 2007;Silva-Corvalán & Montanari, 2008). The primary aim of this previous research has been to determine the age at which children show adultlike distributions of the copulas in production and the age at which they make the temporary v. inherent distinction of certain copula + adjective combinations in comprehension.…”
Section: Acquisition Of Ser and Estarmentioning
confidence: 99%